Blood Cultures: Medicine, Media, and Militarisms - Hannabach, Cathy. author. aut Link
VIII, 153 p. 1 illus.
Keywords: Offering a cultural history of blood as it was mobilized across twentieth-century U.S. medicine, militarisms, and popular culture, Hannabach examines the ways that blood has saturated the cultural imaginary.